Oxidative Stress in Pre-Eclampsia: Bibliometric Visualization Studies and Analysis - Sri Wahyuni, Endang; Wiyono, Nanang; Maryatun, Maryatun; Nurul Mahmudah, Irvina; Duwi Handayani, Juleha; Lutfatul Jannah, Safella (Jurnal Kebidanan Indonesia, 2025)
Background: Preeclampsia is a major cause of death and maternal health problems in the world. Preeclampsia can be triggered by an increase in free radicals which cause oxidative stress. Aim: This study aimed to visually map research publications on the mechanisms of oxidative stress in preeclampsia based on bibliometric analysis. Methods: Systematic Literature Review research design with bibliometric analysis. VOSviewer, Publish or Perish (PoP), and Microsoft Excel resources were used. The database was retrieved from Scopus using the keywords: preeclampsia AND "oxidative stress" AND mechanism as input. Results: The Scopus database revealed a total of 685 published publications on the effects of oxidative stress on preeclampsia from 1996 to 2022. Annual publishing growth is on rising, with 2022 showing the greatest growth rate at 11.68%. The United States has the highest percentage of articles in the world, with a total of 25.8%. The most prolific author is Davidge, ST, with 14 documents. "The effects of oxidative stress on female reproduction: a review", is the most influential article with 928 citations. The International Journal of Molecular Sciences is the most successful journal, with 30 publications and a total link strength of 3988. The University of Mississippi Medical Center is the main institution's research site, with 26 publication documents. The most extensively explored terms are preeclampsia and oxidative stress. Conclusion: The mechanisms of oxidative stress in preeclampsia in the network map were categorized into 5 clusters based on co-occurrence, and “oxidative stress” was the most highlighted term not only in cluster 1 but throughout the network